General Anesthesia vs. Local Anesthesia During Endovascular Treatment for Acute Large Vessel Occlusion: A Propensity Score-Matched Analysis - Han, Hongxing; Wang, Yu; Wang, Hao; Sun, Hongyang; Wang, Xianjun; Gong, Jian; Huo, Xiaochuan; Zhu, Qiyi; Che, Fengyuan (Frontiers in Neurology, 2022)
Abstract Objective: To date, no consensus still exists on the anesthesia strategy of endovascular treatment (EVT) for acute ischemic stroke (AIS) due to large vessel occlusion (LVO). We aimed to compare the 90-day outcomes, puncture-to-recanalization time (PRT), successful recanalization rate, and symptomatic intracranial hemorrhage (sICH) of patients undergoing general anesthesia (GA) or local anesthesia (LA) during the procedure. Methods：Patients were selected from the ANGEL Registry (Acute Ischemic Stroke Cooperation Group of Endovascular Treatment). They were divided into GA group and LA group. The two groups underwent 1:1 matching under propensity score matching (PSM) analysis. Then, 90-day outcomes, PRT, successful recanalization rate, and sICH rate were compared. Results: Among the 705 enrolled patients, 263 patients underwent GA and 442 patients underwent LA. After 1:1 PSM according to the baseline characteristics, each group has 216 patients. Patients with GA had higher median 90-day mRS (3[1-5] vs. 2[1-4], P <0.001), lower 90-day mRS 0-2 rate (43.5% vs. 56.5%, P= 0.007), higher mortality (19.9% vs.10.2%, P= 0.005) and longer PRT (92[60-140] min vs.70[45-103] min, P< 0.001). There were no differences in sICH and successful recanalization rate between both groups. Conclusions: In the real-world setting, LA might provide more outcomes benefit than GA in AIS-LVO patients during the procedure.